2009
DOI: 10.1128/jvi.00434-09
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte and Antibody Responses Reduce Enterovirus 71 Lethality in Mice by Decreasing Tissue Viral Loads

Abstract: Enterovirus 71 (EV71) infects the central nervous system and causes death and long-term neurological sequelae in hundreds of thousands of young children, but its pathogenesis remains elusive. Immunopathological mechanisms have been suspected to contribute to the pathogenesis of neurological symptoms, so antiinflammatory agents have been used to treat patients with neurological symptoms. The present study was therefore designed to investigate the functions of lymphocyte and antibody responses in EV71 infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 23 publications
6
83
2
1
Order By: Relevance
“…These data suggest that the viral loads in throat swabs or stool specimens may not correlate with several T-cell subsets as well as the immune factors in plasma. Lin et al reported that the changes in T-cell subsets exhibited a tissue-specific profile (27). They confirmed that throat swab and stool specimens showed a reduced viral load of EV71 than the specific tissue that is the focus of infection, and thus are not adequate for diagnosis.…”
Section: A B C Dmentioning
confidence: 92%
“…These data suggest that the viral loads in throat swabs or stool specimens may not correlate with several T-cell subsets as well as the immune factors in plasma. Lin et al reported that the changes in T-cell subsets exhibited a tissue-specific profile (27). They confirmed that throat swab and stool specimens showed a reduced viral load of EV71 than the specific tissue that is the focus of infection, and thus are not adequate for diagnosis.…”
Section: A B C Dmentioning
confidence: 92%
“…是手足口病的主要致病原之一, 可使患者并发中枢 神经系统疾病和相关心肺功能衰竭等临床症状, 严 重威胁世界各地婴、幼儿的生命健康,目前尚无有 效药物或疫苗。建立合适的动物模型是深入基础研 究和进行药物评价的关键之一。国内外已有 EV71 感染小鼠的报道, 先后建立了乳鼠 (Lin et al, 2009) 和成年小鼠 (Duo et al, 2009 …”
Section: 手足口病是由肠道病毒引起的传染病 Ev71unclassified
“…The cellular and humoral immune responses, such as represented by T cells and the interleukin-6 (IL-6) driven response, are both essential for decreasing the viral load and mortality in EV71-infected mice. 12,13 In humans, an extensive peripheral and central nervous system inflammatory response, with abnormal IL-10, IL-13 and interferon-c (IFN-c) cytokine production as well as lymphocyte depletion, appears to be responsible for the pathogenesis of EV71-associated pulmonary oedema. [14][15][16] However, to date the mechanism of the cellular immune response to EV71 has not been elucidated in detail.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Blood samples were obtained on days 1-7 after onset, discharge from the hospital (day [7][8][9][10][11][12][13][14] and the fully recovered stage (defined as 1 month after illness onset), respectively. All samples were collected specifically for this study and were coded to protect confidentiality.…”
Section: Recruitment and Sample Collectionmentioning
confidence: 99%